Education, Innovation, and Knowledge Economy in Advancing Sustainable Development Goals: A Multidisciplinary Study - Udoinyang, Nathan; Umoh, Amos Salamat (LP2M Universitas Ibrahimy, 2026)
The study investigates how key elements of the knowledge economy, human capital, innovation systems, ICT infrastructure, and institutional frameworks shape the performance of selected Sustainable Development Goals (SDGs). Drawing on theoretical insights from Endogenous Growth Theory, Schumpeterian Innovation Theory, and Institutional Theory, the research adopts a quantitative design using data obtained from 218 respondents across academia, public-sector agencies, and private organisations. A combination of exploratory and bivariate analyses, with multiple correlations, was applied to investigate these connections. The results reveal that human capital is the most influential determinant of SDG 4 (Quality Education) and SDG 8 (Decent Work and Economic Growth). At the same time, ICT infrastructure is the strongest driver of SDG 9 (Industry, Innovation, and Infrastructure). Institutional fitness significantly contributes to SDG 16 (Peace, Justice, and Strong Institutions) and also moderates the effect of innovation systems on SDG outcomes. Reliability indices (mean Cronbach’s α = 0.87) and sampling adequacy tests (KMO = 0.81) confirm a robust measurement structure. The study concludes that strengthening the pillars of the knowledge economy facilitates broad-based progress toward multiple SDGs simultaneously. Consequently, policymakers should prioritise investments in education, digital technology, innovation ecosystems, and governance reforms to foster inclusive, knowledge-driven, sustainable development.